The use of chatbots in university EFL settings: Research trends and pedagogical implications - Klímová, Blanka; Ibna Seraj, Prodhan Mahbub (Frontiers in Psychology, 2023)
This mini review aims to identify major research trends, models, and theories, and provide specific pedagogical implications for teaching when using chatbots in EFL classes. This study follows the guidelines of the PRISMA methodology and searches for open-access empirical studies in two reputable databases, Web of Science and Scopus. The results of this mini review confirm the findings of other research studies, which show that the present research on the use of chatbots in university EFL settings focuses on their effectiveness, motivation, satisfaction, exposure, and assessment. The key contribution of this study lies in its evaluation of chatbot potential in applying and integrating the existing theories and concepts used in EFL teaching and learning, such as CEFR, mind mapping, or self-regulatory learning theory since none of the review studies before conducted and described such an analysis. Overall, the findings of this mini review contribute with their specific pedagogical implications and methods to the effective use of chatbots in the EFL environment, be it formal or informal.